Ghosts in the dinosaur graveyard - Nahas, Anthony Edwin; Lynch, John (London : BBC Education and Training, 1993)
Expedition og hunting dinosaur's fossil in Gobi Desert in Mongolia
Copy available in DVD format
Executive producer, Philip Clarke ; editor, Jana Bennett
Keywords: Reptiles, Fossil -- Mongolia